Flexible multiterminal photoelectronic neurotransistors based on self‐assembled rubber semiconductors for spatiotemporal information processing. Issue 2 (1st December 2022) - Xu, Yunchao; Zhang, Gengming; Liu, Wanrong; Jin, Chenxing; Nie, Yiling; Sun, Jia; Yang, Junliang
Abstract: A significant step toward constructing high‐efficiency neuromorphic systems is the electronic emulation of advanced synaptic functions of the human brain. While previous studies have focused on mimicking the basic functions of synapses using single‐gate transistors, multigate transistors offer an opportunity to simulate more complex and advanced memory‐forming behaviors in biological synapses. In this study, a simple and general method is used to assemble rubber semiconductors into suspended two‐phase composite films that are transferred to the surface of the ion‐conducting membrane to fabricate flexible multiterminal photoelectronic neurotransistors. The suspended ion conductive film is used as the gate dielectrics and supporting substrate. The prepared devices exhibit excellent electrical stability and mechanical flexibility after being bent. Basic photoelectronic synaptic behavior and pulse‐dependent plasticity are emulated. Furthermore, the device realizes the spatiotemporally integrated electrical and optical stimuli to mimic spatiotemporal information processing. This study provides a promising direction for constructing more complex spiking neural networks and more powerful neuromorphic systems with brain‐like dynamic spatiotemporal processing functions. Abstract : While previous single‐gate synapse devices can mimic the basic functions of synapses, multigate synapse devices provide the opportunity to mimic more complex and advanced memory formation behaviors. Here, a simple self‐assembly and transfer method developed an ion‐gel‐based self‐supported flexible multiterminal synaptic device. The device realizes the spatiotemporal integration during optical and electrical stimulation, enabling the simulation of spatiotemporal information processing.